Modélisation Des Composants D’un Système Hybride Panneaux Photovoltaïque – Stockage D’énergie Via L’hydrogène – Batteries - Boya Bi, Bati Ernest; Gbaha, Prosper; Koffi, Magloire Paul Ekoun; Koua, Kamenan Blaise (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to develop and validate mathematical models of different elements or subsystems of our hybrid power generation system. Each component is modeled as a modular block that can easily be electrically connected to other subsystems. We used the software Matlab®- Simulink R2012a for implementation of our different models. The equations used here are empirical-semi empirical equations and allowed us to model our different components to describe correctly phenomena involved. It was necessary to have data from manufacturer such as polarization curve, surface of an elementary cell, coefficient related to threshold operating parameters, auxiliary consumption parameters and gas stoichiometry. All these allowed us to build under Matlab®-Simulink, photovoltaic panels block, battery pack block, fuel cell block, electrolyzer block and all curves representing different powers produced or consumed and different gases produced or consumed.